Effect of Temperature on Damar Resin-Based Bio-Coating on Mild Steel in Corrosive Media (Acid Effect) by Using Silica from Rice Husk Extract - Luqmanulhakim, M. Naufal; Sulaiman, Fatah; Pramudita, Marta (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2023)
Bio-coating is a natural anti-corrosion coating material that can be easily degraded and renewed. Rice husk extract and damar resin are alternative natural materials believed to have a relatively high silica content, so they can be used as a substitute for synthetic chemicals in protecting metals from corrosion. This research aims to determine the heat resistance ability of bio-coating on mild steel in a 1 M H2SO4 acid corrosive medium. The experimental object used rice husk waste and damar resin as raw materials. The analytical method used is the weight loss method. Damar resin and silica sol, obtained from rice husks' ashing, are mixed to form a homogeneous product. Metal samples coated with bio-coating material were immersed in 1 M sulfuric acid solution, with silica concentrations of 1500 ppm, variation times 1, 3, and 5 hours, and at temperatures of 30, 40, 60, and 80 °C. At 80 °C, the corrosion rate is very high, which proves that the temperature significantly affects the corrosion rate of mild steel immersed in an acid solution. The results showed that the best conditions were four hours of immersion time temperature of 40°C, with an inhibition efficiency of 98%